Different risk factors in identical features of intracranial atherosclerosis plaques in the posterior and anterior circulation in high-resolution MRI. (March 2020) - Xu, Ziqi; Li, Mingyao; Lyu, Jinhao; Hou, Zhikai; He, Jianfeng; Mo, Dapeng; Gao, Feng; Liu, Xin; Sui, Binbin; Shen, Mi; Pan, Yuesong; Wang, Yongjun; et al.
Background: We constructed a high-volume registry to identify whether risk factors of intracranial atherosclerotic plaque (ICAP) features differ in the posterior and anterior circulation in patients with symptomatic intracranial atherosclerotic stenosis (ICAS) investigated by high-resolution magnetic resonance imaging (HRMRI). Methods: The registry was constructed for patients with symptomatic ICAS who underwent HRMRI for culprit plaques. ICAP-vulnerable features included positive remodelling, diffuse distribution, intraplaque haemorrhage and strong enhancement. Results: We analysed risk factors for the same ICAP features between the posterior and anterior circulation in data of 97 patients in the posterior circulation and 105 patients in the anterior circulation ICAPs. In patients with diffuse distribution, the probability of being female were lower [odds ratio (OR):0.08; 95% confidence interval (CI):0.02–0.34; p  = 0.001] and having diabetes mellitus was higher (OR: 7.75; 95% CI:1.75–34.39; p  = 0.007) in posterior circulation patients. In patients with strong enhancement, the probability of having diabetes was higher in posterior circulation patients (OR:6.71; 95% CI:1.37–32.81; p  = 0.019). Conclusions: Our results demonstrate more risk factors in the posterior than in the anterior circulation in patients with the same ICAP-vulnerable features, highlighting the need for stratification of risk factors in symptomatic ICAPs. Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02705599.